Recollection of endemic Rhinacanthus grandiflorus (Acanthaceae) after almost a century - Maity, Rohan; Goswami, Samrat; Shenoy, Akshath; Dash, Sudhansu Sekhar (Phytotaxa, 2025)
Rhinacanthus grandiflorus Dunn (Acanthaceae) was known mainly by its type specimens collected in 1911 by Burkill from the Abor Hills, situated in the state of Indian Himalayan Region (IHR), Arunachal Pradesh. The present paper discusses its recollection after 95 years with a comprehensive morphological account, its distributional status and threat assessment according to IUCN standards.